Apoptosis is increased and cell proliferation is decreased in out-of-phase endometria from infertile and recurrent abortion patients - Meresman, Gabriela Fabiana (2010)
Various endometrial abnormalities have been associated with luteal phase deficiency: a significant dyssynchrony in the maturation of the glandular epithelium and the stroma and a prevalence of out-of-phase endometrial biopsy specimens. Out-of phase endometrium is a controversial disorder related to failed implantation, infertility and early pregnancy loss. Given that the regulation of the apoptotic process in endometrium of luteal phase deficiency is still unknown, the aim of this study was to evaluate cell proliferation, apoptosis and the levels of the main effector caspase, caspase-3 in the luteal in-phase and out-of-phase endometrium.